A common atopy‐associated variant in the Th2 cytokine locus control region impacts transcriptional regulation and alters SMAD3 and SP1 binding. Issue 5 (25th March 2014) - Kretschmer, A.; Möller, G.; Lee, H.; Laumen, H.; von, C.; Schramm, K.; Prokisch, H.; Eyerich, S.; Wahl, S.; Baurecht, H.; Franke, A.; Claussnitzer, M.; et al.
Abstract Background Type 2 immune responses directed by Th2 cells and characterized by the signature cytokines IL4, IL5, and IL13 play major pathogenic roles in atopic diseases. Single nucleotide polymorphisms in the human Th2 cytokine locus in particular in a locus control region within the DNA repair gene RAD50, containing several RAD50 DNase1‐hypersensitive sites (RHS), have been robustly associated with atopic traits in genome‐wide association studies (GWAS). Functional variants in IL13 have been intensely studied, whereas no causative variants for the IL13‐independent RAD50 signal have been identified yet. This study aimed to characterize the functional impact of the atopy‐associated polymorphism rs2240032 located in the human RHS7 on cis‐regulatory activity and differential binding of transcription factors. Methods Differential transcription factor binding was analyzed by electrophoretic mobility shift assays (EMSAs) with Jurkat T‐cell nuclear extracts. Identification of differentially binding factors was performed using mass spectrometry (LC‐MS/MS). Reporter vector constructs carrying either the major or minor allele of rs2240032 were tested for regulating transcriptional activity in Jurkat and HeLa cells. Results The variant rs2240032 impacts transcriptional activity and allele‐specific binding of SMAD3, SP1, and additional putative protein complex partners. We further demonstrate that rs2240032 is located in an RHS7 subunit which itself encompasses repressor activity and might be important for the fine‐tuning of transcription regulation within this region. Conclusion The human RHS7 critically contributes to the regulation of gene transcription, and the common atopy‐associated polymorphism rs2240032 impacts transcriptional activity and transcription factor binding.